NURS-10. IMPROVEMENTS IN A BEHAVIORAL TRAINING AND PHARMACOLOGICAL ANXIOLYSIS ALGORITHM FOR INCREASED COMPLIANCE IN PEDIATRIC PATIENTS IN PREPARATION FOR RADIATION THERAPY: A RETROSPECTIVE ANALYSIS. (4th December 2020) - Tran, Judy; Holt, Jennifer; Crump, Danielle; Shea, Anita; Whetzel, Lin; Lattimore, Andrea; Carson, Rebecca; Anderson, Roberta
Abstract: BACKGROUND: In the pediatric population, the probability of compliance with radiation involves multifactorial elements. Younger pediatric patients often require anesthesia to ensure accurate delivery of radiotherapy. The purpose of this analysis was to refine our algorithm in pediatric patients to better identify children who would benefit from behavioral training and/or anxiolyxis intervention with the goal of minimizing anesthesia use. METHOD: Retrospective data was collected from electronic medical records from 150 pediatric oncology patients <18 years old, treated with photon and proton radiation at our center from August 2016 to December 2019. We identified potential socio-developmental treatment factors thought to impact behavioral compliance and categorized risk factors based on an algorithm to determine risk for noncompliance with radiotherapy. RESULTS: Six categories demonstrated statistical significance (p<0.05) in their influence on behavioral compliance during radiotherapy: age category (specifically age <7: Odds ratio [OR] 3.0, 95% Confidence Interval [CI] 1.0, 9.1), need for sedation with prior imaging studies (p<0.001), parental premonition of requiring anesthesia for successful treatment (p<0.001), duration of treatment, primary language (p<0.001), and use of total body irradiation (OR 3.1, 95% CI 1.1, 9.3). CONCLUSION: Identification of pre-radiation risk factors allowed for better recognition of patients at risk for treatment non-compliance and for requiring daily sedation. Future studies should focus on implementing the algorithm prospectively in an effort to identify and direct early intervention with behavioral training and/or anxiolytics to minimize the need for sedation.